2008
DOI: 10.1136/jnnp.2007.128413
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of GCH1 deletions in Dopa-responsive dystonia

Abstract: We performed a systematic study on the frequency of point mutations and deletions of the gene GCH1 in dopa-responsive dystonia (DRD). A total of 136 dystonia patients were studied. Fifty of these had a sustained response to oral L-Dopa therapy (group 1: definite diagnosis of DRD), whereas the response to L-Dopa was incomplete or not tested in 86 patients (group 2: possible diagnosis of DRD). We found a GCH1 point mutation in 27 patients of group 1 (54%) and in four patients of group 2 (5%). Of these, nine sing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
1
5

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 21 publications
3
39
1
5
Order By: Relevance
“…7,8 The rate of the large GCH1 deletion was very high in Chinese DRD patients (20.1%), especially in the mutation-negative ones testing by gene sequencing (68.4%). Furthermore, the proportion 20.1% is much higher than the 8.0% reported in a European population, 16 which suggests the need to test for the large deletion by multiplex ligation-dependent probe amplification in Chinese DRD patients. The genotype-phenotype correlation analysis did not provide much new information beyond what has been published, probably because the type of mutation and clinical phenotype do not show a strong association in Chinese DRD patients.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…7,8 The rate of the large GCH1 deletion was very high in Chinese DRD patients (20.1%), especially in the mutation-negative ones testing by gene sequencing (68.4%). Furthermore, the proportion 20.1% is much higher than the 8.0% reported in a European population, 16 which suggests the need to test for the large deletion by multiplex ligation-dependent probe amplification in Chinese DRD patients. The genotype-phenotype correlation analysis did not provide much new information beyond what has been published, probably because the type of mutation and clinical phenotype do not show a strong association in Chinese DRD patients.…”
Section: Discussionmentioning
confidence: 70%
“…The large exonic deletion of GCH1 was present in 13 of 62 Chinese patients (20.1%), much higher than the 8.0% reported in a European population. 16 In fact, this large deletion occurred in 13 of 19 (68.4%) mutation-negative DRD patients, who lacked other GCH1 mutation determined by gene sequencing.…”
Section: Clinical Descriptions and Genotypes Of Chinese Drd Patientsmentioning
confidence: 99%
“…Some reports described that a part of patients with dopa-responsive dystonia and clinically diagnosed as Segawa disease did not have any mutation in GCH1 gene. (Zirn et al, 2008) Biochemical diagnose of Segawa disease has also been reported. One method is oral phenylalanine loading test.…”
Section: Wwwintechopencommentioning
confidence: 99%
“…To investigate whether exonic deletions in GCH1 (or other DRD-related genes) contribute to the genetic background of DRD, we performed multiple ligation-dependent probe amplification analyses (MLPA) to search for plausible deletions. MLPA can be used to determine the copy number of up to 50 DNA sequences in a single multiplex polymerase chain reaction (PCR)-based reaction, and it has been widely employed for the detection of exonic deletions including within DRD (Furukawa et al, 2000;Klein et al, 2002;Hagenah et al, 2005;Steinberger et al, 2007;Wider et al, 2008;Zirn et al, 2008;Wu-Chou et al, 2010). In this study, we conducted MLPA analyses on three DRD pathogenic genes in Han Chinese DRD pedigrees and subjects with sporadic DRD to determine whether heterozygous exonic deletions could be found in addition to point mutations.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several studies have indicated that exonic deletions in the GCH1 gene might account for at least some of the cases of DRD (Hagenah et al, 2005;Zirn et al, 2008;WuChou et al, 2010). To investigate whether exonic deletions in GCH1 (or other DRD-related genes) contribute to the genetic background of DRD, we performed multiple ligation-dependent probe amplification analyses (MLPA) to search for plausible deletions.…”
Section: Introductionmentioning
confidence: 99%